Peningkatan Pemahaman tentang Musik Liturgi melalui Katakese Umat di Paroki ST. Darius Riangpuho, Keuskupan Larantuka - Hermania Bhoki; Fernandez, Hendrikus Febrianto (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The Community Service activity targeting the congregation at St. Darius Riangpuho Parish is an important initiative aimed at enhancing the congregation's understanding of liturgical music. This service is based on the congregation's lack of understanding about liturgical music and the demand for the importance of liturgical values. In the Catholic Church, liturgical music is an integral part of the liturgy, aiming to glorify God and sanctify the faithful. The purpose of this service is to improve the understanding of liturgical music and to train the congregation in selecting liturgical songs in accordance with the theme of the Eucharistic celebration. The method employed is Community-Based Participatory Research (CBPR), with an empowerment model grounded in faith. The results of this activity indicate that the congregation now has a deeper understanding of liturgical music and can select songs in line with the theme of the liturgical celebration. The hope is that liturgical music catechesis can be programmed continuously by the parish or diocese to improve the quality of liturgical music in the Eucharistic celebrations.